Efficacy of herbal interventions in oral lichen planus: A systematic review - Ashita R Kalaskar; Rahul R Bhowate; Ritesh R Kalaskar; Sheelpriya R Walde; Rachana D Ramteke; Priyanka P Banode (Wolters Kluwer Medknow Publications, 2020)
Introduction: Oral lichen planus (OLP) is a chronic autoimmune condition requiring prompt treatment to alleviate the signs and symptoms. There is weak evidence emphasizing the efficacy of any one therapy. Steroids, of all the therapies, have proved to be effective and hence considered as the standard care for OLP. However, the complications associated with it further worsen the patient's condition. Alternative safe approaches such as herbal interventions (HIs) have been tried in OLP. Their efficacies could only be evaluated from properly designed research protocols such as randomized controlled trials (RCTs). The present systematic review aims to assess the efficacy of HIs compared to steroids in RCTs involving OLP. Materials and Methods: An extensive search for HIs in OLP was conducted in PubMed, MEDLINE, Cochrane Central Register of Controlled Trials, Scopus, and gray literature. Eight studies fulfilled the eligibility criteria. Results: In all the studies, clinical severity was significantly reduced in within-group comparisons, whereas between-group comparisons showed nonsignificant results, except for total glucosides of paeony capsules. Conclusion: Efficacy of herbal therapy in OLP should be weighed against the high bias in the studies.